2011
DOI: 10.3855/jidc.2108
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in sepsis at time zero: intensive care unit scores, plasma measurements and polymorphisms in Argentina

Abstract: Introduction: A patient's response to sepsis is influenced by their genetic background. Our objective was to use plasma markers, such as protein C (PC), D-dimer, Plasminogen Activator Inhibitor-1 (PAI-1) levels, and the PAI-1 rs1799889 4G/5G and Tumor Necrosis Factor-α rs1800629 G/A polymorphisms to improve classical intensive care unit (ICU) scores. Methodology: We studied 380 subjects, 166 with sepsis. We performed coagulation tests: plasma PAI-1 and PC levels were evaluated by chromogenic methods; and D-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…Previous studies have found higher plasma PAI-1 concentrations in septic patients than in controls [2528], and higher plasma PAI-1 concentrations in non-surviving than in surviving septic patients [312]. In addition, patients with the PAI-1 4G/4G genotype had a higher risk of death than patients with the 4G/5G or 5G/5G genotypes, according to a recently published meta-analysis [21].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous studies have found higher plasma PAI-1 concentrations in septic patients than in controls [2528], and higher plasma PAI-1 concentrations in non-surviving than in surviving septic patients [312]. In addition, patients with the PAI-1 4G/4G genotype had a higher risk of death than patients with the 4G/5G or 5G/5G genotypes, according to a recently published meta-analysis [21].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have found higher plasma PAI-1 concentrations in non-surviving than in surviving septic patients [312]. In addition, the association between PAI-1 4G/5G polymorphism and mortality in septic patients has been studied [1020].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of sepsis studies evaluated other inflammatory mediators, such as TNF and its polymorphisms being associated with increasing stages of sepsis [11,12]. A meta-analysis of two common Toll-like receptor 4 polymorphisms showed no strong correlation with the development of sepsis [13].…”
Section: Timp-1 As a Biomarker In The Icumentioning
confidence: 99%